Efeito da Restauração Ecológica na Recuperação e Conservação da Avifauna em Fragmentos de Mata Ciliar no Rio Uberabinha, em Uberlândia, MG - Carvalho, Dayana Nascimento (2020)
Urbanization causes a replacement of natural vegetation to make room for the growth of cities, influencing local abiotic and biotic changes that affect the quality of life of populations. These changes trigger responses in different animal groups, but especially about birds due to their high sensitivity to anthropogenic changes. In contrast, the presence of green areas in the urban landscape emerges to contribute to the conservation of biodiversity through the establishment of urban parks, squares, gardens, lawns, wooded avenues and riparian forests. For this study, we analyzed the effect of richness, abundance and floristic composition and abiotic factors on the bird community in riparian forest fragments that underwent ecological restoration. We tested the hypothesis that (i) bird richness, abundance and composition are positively correlated with higher richness, abundance and floristic composition of native and zoochoric species; (ii) abiotic factors have seasonal impacts on these relationships. The study was conducted from January to October 2019, in the morning and afternoon. Eight transects of 100 m each, with a distance of 200 m each, were established to sample the birdlife presence in two areas, Praia Clube and Parque Linear Rio Uberabinha. Our results showed that bird richness did not differ significantly between areas, but abundance and composition varied significantly between areas as a function of plant community, partially corroborating our first hypothesis. The most representative trophic guilds were insectivorous, omnivorous and granivorous. The abiotic factors showed significant influence only on the composition of birds when considering the interaction of the season with the area, partially corroborating the second hypothesis. The interactions of birds with plant species showed a higher consumption by native regional and non-regional native species by frugivores of the piscitacidae family. From this perspective, planning and management of the implementation of green areas are important in environments where there is a predominance of generalist and synanthropic species. Considering that many species are dependent on more specific environments such as riparian forests and that some plant species in these areas are important for more specialized bird species, restoration in degraded areas should be planned with the final process of rescuing interactions and conserving the species biodiversity.